Review on Biomimicry levels - Othmani, Nurul Izzati; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah; Abd Rahman, Khairul Aidil Azlin (2018)
To design that inspire from nature, it should not only inspired or follow the form of the characteristic of nature itself. There three levels in Biomimicry, there are Organism Level, Behavior Level and Ecosystem Level. In order to create a design inspired or mimic the nature, these level need to follow and apply in design.However , the widespread and practicalapplication of biomimicry level as a design remains unrealized, commonly the design use biology as a shape which is only using organism level but this is not biomimetic , it has to have some biology in it. The aim of this study is to understand the levels of biomimicry. Content analysis is adopted to identify the level in biomimicry of recreation. The outcome of this study will enhance the understanding of Biomimicry Levels, in order to enhance conditions conducive to life.